Teachers’ challenges in teaching and learning for higher order thinking skills (HOTS) in primary school - Che Seman, Shamilati; Wan Yusoff, Wan Mazwati; Embong, Rahimah (Asian Economic and Social Society (AESS) Publications, 2017)
Malaysian Education Blueprint 2013-2025 aspires to develop Malaysian students who are able to master higher order thinking skills (HOTS) including critical thinking, reasoning, creative thinking, and innovation. The achievement in this area is discouraging, that is, research findings indicated that majority of students were not able to transfer the knowledge they have learnt in the classroom using HOTS to the context outside of the classroom. Studies revealed that teacher was one of the main factors that influenced success or failure in teaching for HOTS. However, the literature on various aspects of teacher factor is still wanting especially in Malaysia. Further, Malaysia had implemented training programs to equip teachers with knowledge and skills to teach for HOTS. Nevertheless, aspects of teachers‟ knowledge of HOTS and competencies in and teaching for HOTS were not explored extensively throughout Malaysia. What is more to explore the challenges faced by teachers in executing HOTS curriculum. Thus, this study was conducted to explore the challenges faced by teachers in teaching and learning for HOTS in the classrooms. It employed qualitative research method to collect and analyze data from interviews conducted with nine teachers who taught Bahasa Melayu (Malay Language), Mathematics, and Science at one of the showcase‟s school of i-THINK program in Terengganu, Malaysia. The transcripts from interview were analyzed thematically to discover the emerging themes. The findings indicated that teachers faced several challenges in teaching and learning for HOTS. The challenges were in the aspects of teachers, teaching and learning preparations and processes, and in the aspects of pupils.